MEASURING POSSIBLE IMPACT OF GNSS INTERFERENCE ON INSTRUMENT APPROACH ON RWY 06 LZZI (Perner's Contacts, 2019)
The article deals with the issue of GNNS signal interference. Authors performed experimental measurements at the Žilina airport, where two sources of GPS L1 signal interference were placed. The goal of the experiment was to confirm or to dispel fears of the increasingly undesirable interference of GNSS signals, particularly near highways and expressways, or other transport infrastructure. GNSS signal interference has a major impact on aviation safety and, in particular, in the context. of the massive introduction of GNSS approach procedures for airports.
Keywords: GNSS; GPS; interferenc; jamming